2010
DOI: 10.1200/jco.2009.25.4367
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Positron Emission Tomography in Patients With Hodgkin's Lymphoma in Unconfirmed Complete Remission or Partial Remission After First-Line Therapy

Abstract: FDG-PET demonstrated 95.9% accuracy in restaging for patients with HL with CRu/PR after first-line therapy. Given the observed probabilities, FDG-PET is highly cost effective and would reduce costs for the public health care program in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…44,45 Because 18 F-FDG-PET/CT is superior to CT alone in evaluating nodal and extranodal involvement, and due to the similarity between PTLD and non-HL[NHL]/HL, 18 F-FDG-PET/CT is routinely used in the diagnostic workup of PTLD patients. Several single-center studies have demonstrated a high sensitivity and specificity for detecting both nodal and extranodal involvement.…”
Section: Staging and Follow-up: What's The Evidence?mentioning
confidence: 99%
“…44,45 Because 18 F-FDG-PET/CT is superior to CT alone in evaluating nodal and extranodal involvement, and due to the similarity between PTLD and non-HL[NHL]/HL, 18 F-FDG-PET/CT is routinely used in the diagnostic workup of PTLD patients. Several single-center studies have demonstrated a high sensitivity and specificity for detecting both nodal and extranodal involvement.…”
Section: Staging and Follow-up: What's The Evidence?mentioning
confidence: 99%
“…In 2009, Fischer et al (21) randomized the investigation by means of CS and MS followed by the in- CT, computed tomography; FDG, fluoro-deoxy-glucose; PET, positron emission tomography; MRI, magnetic resonance imaging; EUS, transesophageal ultrasonography. , and studies approaching analysis of its cost-effectiveness are even rarer (36) . The rational utilization of financial resources is extremely relevant for the public health system, moreover in developing countries such as Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…This was calculated to give a significant ICER of $3268 to detect one case of persistent disease and was simulated to provide a 1% cost saving to HL management if applied across the Brazilian healthcare system. 33 Given the high NPV of intPET, the rates of intPETnegative patients progressing through chemotherapy to become endPET positive are very low. Thus, endPET can be safely excluded in patients who were negative at intPET.…”
Section: Current Controversiesmentioning
confidence: 99%
“…Posttreatment PET is associated with a high NPV (90%) with a PPV of 50-82%, because of false-positive PET findings related to residual inflammatory change. 32,33 The benefit of PET in remission assessment led to its incorporation in the 2007 international working group (IWG) criteria. 34 Residual masses that are PET negative can be safely considered to be complete remission (CR), whereas patients with residual PETpositive lesions should proceed to biopsy wherever possible.…”
Section: Current Controversiesmentioning
confidence: 99%